Problematika Guru dalam Pembelajaran PAI pada Kurikulum Merdeka di SMK Negeri 1 Tanjung Raya - Ayunda, Annisa Desri; Wati, Salmi; Ilmi, Darul; Fauzan, Fauzan (Faidatuna, 2024)
The aim of the research is to find out the problems faced by PAI teachers in implementing the independent curriculum, as well as to find out what solutions PAI teachers use to overcome the problems faced in learning Islamic Religious Education in the independent curriculum at vocational schools. Negeri 1 Tanjung Raya. To achieve the above objectives, a descriptive qualitative research approach was used with a case study type approach, based on the problem formulation, objectives and benefits of the research. The key instrument is the PAI teacher and the supporting informants are the school principal and head of curriculum at SMK Negeri 1 Tanjung Raya. The data collection techniques used were interviews and documentation. After that the data was analyzed by source triangulation, namely by comparing the results of the interview with the data obtained. The results of the research show that the problems experienced by PAI teachers are: (1) difficulty changing old habits and thought patterns because they are used to the 2013 Curriculum. (2) Lack of teacher readiness in differentiated learning is influenced by limited references. (3) there is no awareness of students to play an active and creative role. (4) limited learning support facilities. Solutions implemented by teachers include: attending workshops, seminars and training related to the Independent Curriculum, sharing experiences with other teachers, and providing motivation for students to be active and creative in learning.